SOCIOLINGUISTIC PERSPECTIVE OF DIALECTAL VARIATION IN CONTEMPORARY ENGLISH - Aliyeva Navruza Khabibullayevna (International Journal of Literature and Language Studies, 2026)
Abstract. This paper investigates dialectal variation in contemporary English from a sociolinguistic perspective. English, as a global language, demonstrates extensive variation influenced by geographical, social, historical, and cultural factors. The study explores major types of English dialects, including regional, social, ethnic, and global varieties commonly known as World Englishes, and examines how variation manifests at phonological, lexical, and grammatical levels. A qualitative descriptive methodology is applied, based on secondary linguistic literature and comparative analysis of established English varieties.